The impact of self-disclosure on EFL students' Motivation, Participation, and Writing proficiency in Higher Education in Morrocco : The case of the Fez Dhar El Mahraz Department of English - Jebbour Mohsine (Université Sidi Mohammed Ben Abdellah, Faculté des Sciences - Dhar El Mahraz, Fès, 2018)
The purpose of this quasi-experimental study was to test the impact of self-disclosure on EFL students’ motivation, participation, and writing proficiency at the Faculty of Arts and Humanities, Fez Dhar El Mahraz. Self-disclosure refers to teachers’ and/or students’ verbal communication of personal feelings, opinions, and experiences that are positive in nature and/or relevant to the course content in class. The sample of this study consisted of undergraduate learners enrolled in the department of English. Mixed methods in data collection and analysis were employed to answer three research questions. First, 87 students in the experimental group—after receiving self-disclosure as treatment—and 87 students in the control group completed a questionnaire in order to know their level of motivation. Additionally, 15 students from the experimental group were interviewed to elicit their perceptions of the effects of self-disclosure. Though the questionnaire results showed that the experimental group’s level of motivation was not found to be higher than that of the control group, the interviewees believed that teacher self-disclosure leads to favorable attitudes toward instructors, and student self-disclosure helps develop favorable attitudes toward classmates and feelings of intrinsic motivation. Second, results from the observation of six English sessions and 214 students’ responses to a questionnaire suggested that teacher self-disclosure helped create classroom participation by encouraging teacher-students interaction and increasing the learners’ freedom to engage in class discussion. Third,19 students were tested before and after writing about six self-disclosure topics; the results indicated that the participants’ expression of their self-disclosures did not help improve their writing proficiency in terms of producing a higher amount of accurate and complex sentences. Overall, such findings suggested that language teachers need to be aware of when and how to implement self-disclosure as a pedagogical practice in class to engage students in a fruitful learning experience.
Keywords: Langue et Littérature Anglaise; Class participation; EFL Student; Self-disclosure; Writing proficiency